Medicalization, Prevention and Healthy Bodies: The Topicality of the Contributions of Illich and Foucault [Medicalización, Prevención y Cuerpos Sanos: La Actualidad de Los Aportes de Illich y Foucault] - Aurenque-Stephan, D; De la Ravanal-Gomez, M (Universidad Panamericana, 2018)
Following the analysis of Illich and Foucault, it is argued that the development of modern medicine occurs parallel to a profound medicalization that leads to important changes in the meaning of the body and health. One of the most paradigmatic current expressions of these transformations is observed in technologies for preventive medicine, inasmuch as it contributes not only to dilute the subjective experience of health and disease, but also disposes the body for sophisticated forms of control and power. The aim of this study, however, is not to demonize all preventive practices, but rather to denounce medicalization as a growing problem and to offer theoretical and philosophical elements that allow us to have a better understanding of this phenomenon and unveil some of its hidden normative foundations. © 2018 Universidad Panamericana. All rights reserved.